I'll be home for Christmas [videorecording (DVD)] - Hoberman, David, 1953-; Trench, Tracey; Nursall, Tom; Goldberg, Harris; Sanford, Arlene; Thomas, Jonathan Taylor; Biel, Jessica, 1982-; Cole, Gary, 1956-; Narita, Hiro, 1941-; Allin, Michael, 1944- (Disney DVD., 2002)
A self-centered college student has one thing on his mind--get home for Christmas. Just days before his deadline he wakes up in the California desert--stranded and penniless, wearing a Santa suit and a white beard glued to his face! The closer Jake gets to home, the closer he gets to the true meaning of Christmas and Family in this nonstop comedy of errors.